Occupational Health Services Improve Effective Coverage for Hypertension and Diabetes Mellitus at Japanese Companies - ITO, Masato; HASHIGUCHI, Katsuyori; FUJINO, Yoshihisa; NAGATA, Tomohisa; MORI, Koji; NAGATA, Masako (Journal of UOEH, 2019)
The World Health Organization (WHO) aims to enable all people to receive health services, and has proposed effective coverage (EC) as an index for this aim. EC refers to “the fraction of potential health gain that is actually delivered to the population through the health system, given its capacity,” and is used to indicate the percentage of the population whose diseases are well controlled among those who require treatment or are receiving treatment. This study aimed to evaluate the effects of occupational health services on EC. We hypothesized that occupational health services provided to employees by full-time occupational health practitioners, such as occupational physicians and occupational health nurses, improve EC for hypertension, diabetes mellitus and hyperlipidemia compared to those services provided by part-time occupational health practitioners. We conducted a cross-sectional study to analyze the results of general medical examinations, personnel information, and medical expense claims in fiscal year 2011. A total of 91,351 male employees at a company group participated in the study. The EC for hypertension, diabetes mellitus and hyperlipidemia was measured and compared between the employees in workplaces with occupational health practitioners (OH group) and the employees in workplaces without occupational health practitioners (non-OH group). The EC for hypertension and diabetes mellitus was significantly greater in the OH group than in the non-OH group (aOR: 1.41, 95% CI: 1.20 - 1.66 for hypertension; aOR: 1.53, 95% CI: 1.17 - 2.00 for diabetes mellitus), while the EC for hyperlipidemia was comparable (aOR: 1.11, 95% CI: 0.92 - 1.34). Occupational health services provided by full-time occupational health practitioners greatly improve health management after a medical examination.